Ethanol from maize hybrids in Brazil - Eckert, Caroline Thaís; Frigo, Elisandro Pires; Albrecht, Leandro Paiola; Albrecht, Alfredo Junior Paiola; Silva, Andre Felipe Moreira; Dos Santos, Weslei Gomes; Cesco, Victor José Salomão [UNESP]; Dieter, Jonathan; Piccin, Emanuele Scapin (FapUNIFESP (SciELO), 2023)
The aim was to investigate the differences between maize hybrids for their agronomic yield and their agro-energy potential. The study was conducted in Palotina and Assis Chateaubriand, Paraná, Brazil. The treatments were composed of 10 maize hybrids (DKB290 [non-GMO], DKB315, DKB340, DKB290, Formula, Defender, Status, 2B810, 30F53, BG7330), which were evaluated for grain moisture and yield, starch content, total soluble solids content, ethanol content in the juice and ethanol yield. The important factors for the result are related to grain yield and the quality of the harvested grains, and agronomic performance of these hybrids may differ according to each crop year. Hybrid 30F53 stood out positively for all variables. Hybrid DKB315 showed the highest ethanol yield and high grain yield, and insignificant grain quality was not enough to result in a decline in ethanol yield.
Keywords: biofuel; ethanol yield; genotype; grain yield; Zea mays L